2013
DOI: 10.4319/lom.2013.11.360
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying photosynthetic rates of microphytobenthos using the triple isotope composition of dissolved oxygen

Abstract: Microphytobenthos are important mediators of nutrient and carbon fluxes in coastal environments. However, quantifying production rates by microphytobenthos is difficult, and existing methods necessitate perhaps erroneous assumptions that dark respiration equals light respiration. Here we present a new method for quantifying photosynthetic rates of microphytobenthos, i.e., gross primary production, by using the triple isotope composition of dissolved oxygen in benthic flux chambers. Because the triple oxygen is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…NEP and respiration in the mesocosms were similar to rates from Waquoit Bay (Rao and Charette 2011;Stanley and Howard 2013), suggesting the experimental system adequately mimicked field conditions. Both trophic history and nutrient treatments influenced sediment metabolism (Table 2; Fig.…”
Section: Mesocosm Experimentsmentioning
confidence: 65%
“…NEP and respiration in the mesocosms were similar to rates from Waquoit Bay (Rao and Charette 2011;Stanley and Howard 2013), suggesting the experimental system adequately mimicked field conditions. Both trophic history and nutrient treatments influenced sediment metabolism (Table 2; Fig.…”
Section: Mesocosm Experimentsmentioning
confidence: 65%
“…O 2 is distributed heterogeneously within the pond, reflecting the spatial variability of production; a survey of O 2 around the perimeter of the study pond revealed peak O 2 of 200% to 300% of saturation in areas with visible benthic algae or vascular plants. Photosynthetic O 2 production tracks photosynthetically active radiation (PAR, 400–700 nm; Stanley & Howard, ; Howard, ), and local O 2 supersaturation may form bubbles at nucleation points (such as photosynthesizing algae).…”
Section: Resultsmentioning
confidence: 99%
“…Because the respiration and GPP rates from EC measurements are conservative estimates due to the assumption that daytime and nighttime respiration is equivalent (Hume et al 2011, Long et al 2013, further in situ research is required to evaluate how respiration rates influence C storage in seagrass beds. In future studies, the EC determination of respiration and GPP could be improved by comparisons with other techniques that specifically determine the daytime respiration or GPP, such as triple oxygen isotopes (Stanley & Howard 2013).…”
Section: Florida Bay Gradientsmentioning
confidence: 99%